Relationship of Placental Vascular Indices with Macroscopic, Histopathologic, and Intraoperative Blood Loss in Placenta Accreta Spectrum Disorders - Mohammad Adya Firmansha Dilmy; Yuditiya Purwosunu; Yudianto Budi Saroyo; Tantri Hellyanti; Noroyono Wibowo; Damar Prasmusinto; Rima Irwinda; Victor Prana Andika Santawi; Hizkia Mangaraja Hasiholan; Rabbania Hiksas (Hindawi Limited, 2022)
Introduction. Placenta accreta spectrum is an obstetrical complication with a high level of morbidity. The 3-dimensional (3D) power Doppler method has been widely used to improve the diagnosis. Therefore, this study aims to elucidate better the relationship of quantitative placental vascular indices towards macroscopic findings, histopathological grading, and intraoperative blood loss in the disorder. Methods. A preliminary study using a cross-sectional design was conducted on 34 clinically diagnosed women with PAS. The 3D power Doppler with the VOCAL II software was used to measure the level of vascularization index (VI), flow index (FI), and vascularization flow index (VFI). Gross anatomical appearance and histopathology results were categorized as accreta, increta, and percreta. In addition, the intraoperative blood loss level was measured, and 1500 mL was the cutoff for massive hemorrhage. Results. The vascularity indexes were VI = 44.2 (23.7-74.9), FI = 35.4 (24.9-57), and VFI = 15.3 (8.5-41.7). The FI value was significant in comparing gross pathological stages (p=0.015) and had a moderate positive correlation in relation to blood loss (r = 0.449). VI, FI, and VFI above the cutoff values were shown to be strongly associated with blood loss ≥ 1500 cc with aOR 7.00 (95% CI 1.23-39.56), aOR 10.00 (95% CI 1.58-63.09), and aOR 9.16 (95% CI 1.53-54.59), respectively. Conclusion. This preliminary study demonstrated an initial potential of the FI value from 3D USG power Doppler to predict the depth of PAS invasion before surgery and intraoperative blood loss level.